1994
DOI: 10.1002/jmv.1890420305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against hepatitis e virus among urban and rural populations in Venezuela

Abstract: Antibodies against hepatitis E virus (HEV) were detected in sera by a synthetic peptide-based enzyme immunoassay (EIA) from different populations in Venezuela. Antibodies against HEV were found in 1.6% (3/184) of urban pregnant woman (Caracas), in 3.9% (8/204) of rural populations (San Camilo, Edo Apure), and in 5.4% (12/223) of rural Amerindians (Padamo, Edo Amazonas). Positivity was confirmed by a neutralization EIA based on the use of competing soluble free peptides. The prevalence of antibodies in the Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 9 publications
2
25
0
4
Order By: Relevance
“…Meanwhile, residents in rural areas in Rio de Janeiro (Sumidouro) had a similar seroprevalence (2.1%; 95% CI, 0.5-6.4) 7 . Regarding studies conducted in rural populations in Latin America, similar anti-HEV IgG prevalence rates were also reported in Bolivia (6.3%; 95% CI, 3.6-10.3) 11 and Venezuela (5.4%; 95% CI, 2.9-9.4) 12 , but a higher rate was reported in Mexico (36.6%; 95% CI, 31.0-42.7) 13 . Differences in regional endemicity, risk characteristics, and the performance of diagnostic assays for hepatitis E are the possible reasons for these differences in the observed rates.…”
supporting
confidence: 63%
“…Meanwhile, residents in rural areas in Rio de Janeiro (Sumidouro) had a similar seroprevalence (2.1%; 95% CI, 0.5-6.4) 7 . Regarding studies conducted in rural populations in Latin America, similar anti-HEV IgG prevalence rates were also reported in Bolivia (6.3%; 95% CI, 3.6-10.3) 11 and Venezuela (5.4%; 95% CI, 2.9-9.4) 12 , but a higher rate was reported in Mexico (36.6%; 95% CI, 31.0-42.7) 13 . Differences in regional endemicity, risk characteristics, and the performance of diagnostic assays for hepatitis E are the possible reasons for these differences in the observed rates.…”
supporting
confidence: 63%
“…In Venezuela, Puyol et al (1994) reported seroprevalence rates ranging from 1.6 to 5.4% in three different populations (pregnant women of urban area, rural people and Amerindians).…”
Section: Seroprevalence In Humans and Pigsmentioning
confidence: 99%
“…También se han hecho algunos estudios en población indígena en Bolivia, Venezuela y Chile, en los cuales se ha demostrado una seropositividad para HEV entre 5,4 y 20,1 % (27,32,34,35). En trabajos realizados en Chile y Perú en grupos de riesgo, como trabajadores de la salud, presidiarios y operarios del sistema de agua y alcantarillado, se detectaron anticuerpos anti-HEV en un rango de 7,5 a 12,5 % de las muestras (36).…”
unclassified